A Pilot Study on Effects of Acupuncture and Moxibustion by Hyperspectral Imaging Technique. (2nd December 2014) - Zhang, Dong; Li, Yin-long; Wang, Shu-you; Bai, Xiao-dong; Song, Xiao-jing; Li, Shun-yue
Abstract : This study was to observe the effects of acupuncture and moxibustion on spectrum features of acupoint using hyperspectral imaging (HSI) technique. HSI of the Neiguan (PC6) in the acupuncture groups, moxibustion groups, and control groups was scanned by the hyperspectral imager to analyze the spectrum features and the variations within the wavelength of 400–1000 nm and explore the relationship between the spectral characteristics and effects of acupuncture and moxibustion. The light absorption intensity was slightly reduced within the wave band of 540–590 nm after acupuncture. The absorption intensity of PC6 before moxibustion was significantly higher than that after moxibustion, and the maximum reduction was found at the wavelength of 580 nm with 20.5% reduction, P < 0.05 . There was no significant change of the spectrum of palm and PC6 and the spectrum curves of the acupoint were basically identical in control group. The light absorption intensity of PC6 of human body was weakened after Acu-mox. Specific wavelengths were all exhibited at 580 nm and the effect of moxibustion was more significant. HSI technique can be used to measure the spectral characteristics of the acupoint areas. This first time research would be significant and beneficial for study on the effect of acupuncture and moxibustion.